Profil Kadar Glukosa Darah pada Lansia di Kecamatan Rambipuji Kabupaten Jember - Desi Wulandari; fina Lanahdial Husna; Aulia Fitri (Jurnal Analis Kesehatan Kendari, 2026)
Elderly individuals are a population group vulnerable to increased blood glucose levels due to the aging process, decreased insulin sensitivity, and changes in body metabolism. Random blood glucose (RBG) examination is important as an early detection effort for hyperglycemia and diabetes mellitus in the elderly. The objective of this academic inquiry was to delineate random blood glucose levels within geriatric populations according to age and gender. The investigation executed an observational technique utilizing a cross-sectional methodology. The selected cohort comprised 25 advanced-age participants whose random blood glucose levels were quantified a single time utilizing capillary blood samples. Collected information underwent statistical summarization via frequency distribution and percentages. The empirical outcomes demonstrated that subjects within the 60–74 years bracket accounted for 17 individuals (68%), whereas those within the 75–90 years classification constituted 8 persons (32%). Categorized by gender, 19 participants (76%) were female and 6 subjects (24%) were male. Normal blood glucose levels were identified in 13 examinees (52%), whereas elevated blood glucose levels were documented in 12 candidates (48%). The 75–90 years generational cluster exhibited an increased ratio of elevated blood glucose levels, mounting to 62.5%. In relation to gender, males demonstrated a superior fraction of elevated blood glucose levels (66.7%) parallel to females (42.1%). Practically half of the senior enrollees manifested elevated blood glucose levels. Older elderly individuals and males had a higher proportion of hyperglycemia compared to other groups. Routine blood glucose examination and the implementation of a healthy lifestyle are necessary to prevent complications of diabetes mellitus in the elderly.